Abnormal nocturnal behavior due to hypoglycemia: A case report. Issue 6 (February 2019) - Weng, Ning; Luo, Yan-Wen; Xu, Jian-dong; Zhang, Yue
Abstract: Rationale: Hypoglycemia, which is characterized mainly by palpitations, dizziness, and sweating, is common and easy to identify. However, some other symptoms, such as mental disorder or abnormal behavior, are atypical, which may lead to a misdiagnosis of epilepsy, sleepwalking, infarction, or mental disorder, among others. Patient concerns: We report a case of a patient with type 2 diabetes who presented with abnormal nocturnal behavior due to hypoglycemia. Diagnosis: Hypoglycemia was diagnosed based on a blood glucose level of 2.1 mmol/L when the patient turned up disoriented unresponsive, unable to understand what was said to him, and producing nonsensical speech. After the patient ate a piece of chocolate, his consciousness returned to normal and all mental symptoms disappeared. Polysomnography (PSG) was synchronously performed. The results of the PSG did not show any signs of abnormality during nonrapid eye movement (NREM) or rapid eye movement (REM) sleep. Interventions: We regulated his dose of insulin. Outcomes: No additional episodes occurred during the 3-month follow-up. Therefore, the abnormal nocturnal behavior of this patient was determined to be due to hypoglycemia, while the cause of the hypoglycemia was insulin overuse. Lessons: For physicians, if the cause of abnormal behavior cannot be detected, hypoglycemia should be suspected. Long-term persistent hypoglycemia may cause brain dysfunction and even result in permanent brain damage.